Development of Hemorrhagic Septicemia Vaccine - Singh, V. P.; Gupta, S. K. (Indian Farming, 2015)
Identification of the major protective antigens in Pasteurella multocida serogroup B is required to develop the new generation vaccines. The genomic and proteomic studies of Pasteurella multocida serotype B:2 with the help of bioinformatics is necessary to identify the novel immunogen for candidate vaccine antigen. The use of adjuvants, including the new generation adjuvants, should be evaluated to give an easily injectable vaccine. Furthermore, investigations into the immune mechanisms, virulence determinants, and the carrier state are some important areas that have been suggested as future line of research.